2008
DOI: 10.1128/jb.01823-07
|View full text |Cite
|
Sign up to set email alerts
|

Differential Substrate Specificity and Kinetic Behavior of Escherichia coli YfdW and Oxalobacter formigenes Formyl Coenzyme A Transferase

Abstract: The yfdXWUVE operon appears to encode proteins that enhance the ability of Escherichia coli MG1655 to survive under acidic conditions. Although the molecular mechanisms underlying this phenotypic behavior remain to be elucidated, findings from structural genomic studies have shown that the structure of YfdW, the protein encoded by the yfdW gene, is homologous to that of the enzyme that mediates oxalate catabolism in the obligate anaerobe Oxalobacter formigenes, O. formigenes formyl coenzyme A transferase (FRC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…Without YfdU-catalyzed decarboxylation, hydrolysis of the oxalyl-CoA thioester would result in a reduction of the formyl-CoA pool and no net removal of oxalate. High specificity for formyl-CoA and oxalate makes it unlikely that the hydrolysis of succinyl-CoA (or other CoA derivatives) is significant in the yfdU mutant (44,45).…”
Section: ϫ5mentioning
confidence: 99%
See 1 more Smart Citation
“…Without YfdU-catalyzed decarboxylation, hydrolysis of the oxalyl-CoA thioester would result in a reduction of the formyl-CoA pool and no net removal of oxalate. High specificity for formyl-CoA and oxalate makes it unlikely that the hydrolysis of succinyl-CoA (or other CoA derivatives) is significant in the yfdU mutant (44,45).…”
Section: ϫ5mentioning
confidence: 99%
“…YfdW from E. coli is a formyl-CoA transferase (44), and YfdU is an oxalyl-CoA decarboxylase (45,46). YfdW and YfdU are homologous to FRC and OXC, two essential metabolic proteins from the obligate anaerobe Oxalobacter formigenes (47).…”
mentioning
confidence: 99%
“…Type III CoA transferases, such as the crotonoyl-CoA ( caiB ) and yfdW gene products from E. coli (19)(20)(21) as well as the formyl-CoA transferase (FRC) from Oxalobacter formigenes ( 22 ), share a conserved Asp 169 residue (D169 formyl CoA) involved in catalytic formation of oxo-acid mixed anhydrides as well as covalent CoA thioesters. The baiF and baiK gene products share this conserved residue ( Fig.…”
Section: Cloning Expression and Purifi Cation Of Bile Acid Coa Tranmentioning
confidence: 99%
“…Recently, Toyota et al (2008) confirmed experimentally that the gene YfdW from E. coli was a formyl-CoA transferase. Oxalyl-CoA decarboxylase gene oxc (synonym yfdU) is also present in E. coli K12, so this organism could at least be an oxalate-oxidizing bacterium.…”
Section: Frc Amplification From Pure Strainsmentioning
confidence: 60%
“…These genes were first identified in the anaerobe O. formigenes but occur in aerobes as well (Hokama et al, 2005;Toyota et al, 2008).…”
Section: Introductionmentioning
confidence: 99%